2008
DOI: 10.1124/jpet.108.137927
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin InhibitsStaphylococcus aureusHost Cell Invasion through Modulation of Isoprenoid Intermediates

Abstract: Patients on a statin regimen have a decreased risk of death due to bacterial sepsis. We have found that protection by simvastatin includes the inhibition of host cell invasion by Staphylococcus aureus, the most common etiologic agent of sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 41 publications
5
71
0
Order By: Relevance
“…In the current study, infectioninduced increase in tissue factor concentration was also attenuated in the simvastatin-treated group. This may have been secondary to the inhibition of S. aureus invasion of endothelial cells and macrophages, as suggested by other reports [4,5,28,29]. Finally, tissue factor levels could have been attenuated by the enhancement of the protein C pathway, as this pathway down-regulates the pro-coagulant tendency induced by sepsis [25].…”
Section: Discussionmentioning
confidence: 60%
“…In the current study, infectioninduced increase in tissue factor concentration was also attenuated in the simvastatin-treated group. This may have been secondary to the inhibition of S. aureus invasion of endothelial cells and macrophages, as suggested by other reports [4,5,28,29]. Finally, tissue factor levels could have been attenuated by the enhancement of the protein C pathway, as this pathway down-regulates the pro-coagulant tendency induced by sepsis [25].…”
Section: Discussionmentioning
confidence: 60%
“…Previous work had indicated that simvastatin inhibits endocytic uptake that is dependent on the precise localization of small-GTP-ases within cellular membranes [14,15,26,27]. Although incompletely understood, transfer of biomolecules to the acceptor cell relies in part on endocytic uptake [17].…”
Section: Resultsmentioning
confidence: 99%
“…For the majority of studies, the strain used was ATCC 29213 (American Type Culture Collection, Manassas, VA). This strain induces sepsis in vivo [13] and is invasive [14,15]. To investigate the role of invasion, minimally invasive ATCC 700699 also was examined.…”
Section: Methodsmentioning
confidence: 99%
“…At subinhibitory concentrations, statins reduce biofilm formation in P. aeruginosa , S. aureus and Staphylococcus epidermidis [8991], and suppress production of S. aureus cytolysins alpha-toxin and Panton-Valentine leukocidin [90]. Statins may also block host epithelial or endothelial cell invasion by P. aeruginosa , S. aureus , or the neonatal pathogen group B Streptococcus [9294]; the later study suggesting that mevastatin antagonism of Rho-family GTPases involved in endocytotic uptake might inhibit pathogen host cell entry.…”
Section: Statins: Repurposing a Leading Human Medication At The Host-mentioning
confidence: 99%